Dinâmica da transmissão de linhagens genotípicas de Mycobacterium tuberculosis multidroga resistentes e sensíveis às drogas antituberculose em Fortaleza-Ceará - Luiz, Roberta dos Santos Silva (2012)
The tuberculosis (TB) disease is caused by the bacillus Mycobacterium tuberculosis, which is transmitted by aerosols of patients with active tuberculosis. About two billion people are infected worldwide, with 3.6% of multidrug resistant TB, which means resistant to rifampicin and isoniazid. To control this disease, is necessary the early diagnosis, treatment, and chemoprophylaxis of susceptible individuals, and is also essential monitoring of sensitive strains (S) and the emergence of resistant strains (R). This study investigated the transmission dynamics of tuberculosis (TB) by analyzing clinical, phenotypic and genetic diversity of clinical strains of M. tuberculosis. The study was cross-sectional in patients with pulmonary TB in an ambulatory reference of Fortaleza, from January 2007 to March 2008. Demographic and clinical information of places of social aggregation of patients and their contacts and co-morbidities were obtained by structured questionnaire. We conducted sensitivity test to anti-TB drugs, genotyping and spoligotyping georeferencing of the cases. Of the 138 patients studied, 74 were TB-S and 64 (46.37%) were resistant to at least one of the drugs tested (TB-R). We found a high frequency of M. tuberculosis drug-resistant among previously treated cases (84%) compared to new cases (16%, P <0.001). Among 115 isolates of M. tuberculosis genotyped, 74 (64%) were grouped into 22 lines of standard spoligotyping, while 41 (36%) isolates were identified as new genotypes (new). The more frequently families found were Latin-American Mediterranean (LAM) (33%), Haarlem (H) (12%) and Universal (U) (5%). The distribution of the families spoligotypes was similar to that found in South America. There was no significant association between the geographic distribution of patients with TB-R, TB-S and with different families spoligotypes. The geospatial analysis revealed 24 patients (23%) who shared the same residence or lived close to a case. Among those living with the same household, they had the same pattern and genotypic resistance. Out of the results of this study, it was observed that the resistance to drugs anti-TB among the studied cases was predominantly type secondary; however, some cases were the primary resistance. Therefore, it is necessary a more effective monitoring program in order to reduce TB cases in Fortaleza.